STRATEGIC DECISION MAKING FOR BUSINESS DEVELOPMENT AND PROFIT OPTIMIZATION USING THE ANALYTICAL HIERARCHY PROCESS: THE CASE OF KLINIK PRATAMA SINDANG SARI - Reza Yudha Fadillah; Meditya Wasesa (LPPM STIE Muhammadiah Bandung, 2025)
Health is important for the well-being of the community, and basic clinics are important places for people in Indonesia to get health treatment. Klinik Pratama Sindang Sari has been committed to providing great service since it opened in 1997. In 2024, it received